Chromium-doped ternary material precursor, ternary material and preparation method and application thereof
By adding chromium salt and adjusting the pH value during the sintering process, the chromium doped three -yuan front -drive body is prepared to solve the problem of uneven distribution of mixed elements, realizing the porous structure and high ratio area of the ternary material, which increases The performance of lithium ion battery.
Patent Information
- Application Number
- CN202411484407.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art has uneven distribution of doped elements during the sintering process, resulting in unsatisfactory doping effect, and the method of preparing porous and high specific surface area positive electrode materials is cumbersome and difficult to control.
After reacting the nickel, cobalt and manganese solution, chromium salt is added, the pH value of the reaction system is adjusted, the chromium-doped ternary material precursor is prepared by aging, and is mixed and sintered with the lithium source to prepare the ternary material.
The uniform doping of chromium is realized, and the ternary material with a porous structure and high ratio surface area is prepared, which improves the transmission rate and energy density of lithium ion, and the process is simple and easy.
Smart Images

Figure CN119349663A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a chromium-doped ternary material precursor, a ternary material, and a preparation method and application thereof. Background Art
[0002] With the rapid development of lithium-ion batteries in new energy vehicles and energy storage, lithium-ion batteries with higher cost-effectiveness, higher specific capacity and better cycle stability are needed. As the core material of lithium-ion batteries, positive electrode materials play a decisive role in improving the performance of lithium-ion batteries. Among them, ternary materials have the advantages of stable voltage and high capacity. Further doping elements can improve the electrochemical performance and cycle stability of positive electrode materials. The method of doping positive electrode materials in the prior art is to add the doped elements during the sintering process, which can easily cause the disadvantages of uneven distribution of doped elements and poor doping effect.
[0003] Ternary materials are secondary particles formed by the accumulation of small primary particles. In order to speed up the transmission rate of lithium ions, the existing technology prepares porous, high specific surface area positive electrode materials to increase the contact area with the electrolyte, but the preparation method is difficult and the steps are cumbersome. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art that doping elements during the sintering process easily leads to unsatisfactory doping effect, and the prior art is cumbersome and difficult to control when preparing porous, high specific surface area positive electrode materials, thereby providing a chromium-doped ternary material precursor, ternary material and its preparation method and application.
[0005] To this end, the present invention provides the following technical solutions.
[0006] The present invention provides a method for preparing a chromium-doped ternary material precursor, comprising the following steps:
[0007] (1) preparing an intermediate product by reacting a nickel-cobalt-manganese solution; the reaction time is 10-30 hours;
[0008] (2) adding a nickel-cobalt-manganese solution and a chromium salt to the intermediate product simultaneously, reacting, adjusting the pH of the reaction system, and aging to prepare a chromium-doped ternary material precursor;
[0009] Wherein, before adjusting the pH of the reaction system, the following conditions are met: pH ≤ 12;
[0010] The pH of the reaction system was adjusted to satisfy: 12<pH≤14.
[0011] In an optional embodiment, before adjusting the pH of the reaction system, the following conditions are satisfied: 10.8 < pH ≤ 12;
[0012] The pH of the reaction system is adjusted to meet the following conditions: 12<pH≤14;
[0013] In an optional embodiment, the aging time is 5-18h;
[0014] In an optional embodiment, the nickel-cobalt-manganese solution in step (1) and the nickel-cobalt-manganese solution in step (2) have the same concentration.
[0015] In an optional embodiment, the steps of preparing the nickel-cobalt-manganese solution specifically include: mixing a nickel source, a cobalt source and a manganese source;
[0016] In an optional embodiment, in step (2), the reaction time is 30-70h;
[0017] Preferably, the chromium salt comprises a soluble chromium salt;
[0018] Preferably, the soluble chromium salt comprises at least one of chromium nitrate, chromium sulfate and chromium trichloride;
[0019] Preferably, in step (2), the molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions in the reaction solution to the chromium ions is 1:(0.8-1.2).
[0020] It should be noted that in step (2), the nickel-cobalt-manganese solution and the chromium salt are added while reacting; in step (2), the molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions in the reaction solution to the chromium ions is 1:(0.8-1.2) refers to the molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions in the nickel-cobalt-manganese solution added in step (2) to the total amount of chromium ions in the chromium salt added.
[0021] In an optional embodiment, the step (1) further comprises adding at least one of a precipitant and a complexing agent before carrying out the reaction;
[0022] Preferably, the complexing agent includes at least one of ammonia, urea and ammonium bicarbonate;
[0023] Preferably, the precipitant comprises at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide;
[0024] In an optional embodiment, the concentration of the precipitant is 4-12 mol / L;
[0025] In an optional embodiment, the concentration of the complexing agent is 1-5 mol / L;
[0026] Before adjusting the pH of the reaction system, the pH value is adjusted by using a precipitant and a complexing agent.
[0027] After adjusting the pH of the reaction system, the pH value of the reaction system is adjusted by a pH adjusting agent, which is commonly used in the art, such as ammonia water, sodium hydroxide solution, and the like.
[0028] Preferably, the molar ratio of nickel ions, cobalt ions and manganese ions in the nickel-cobalt-manganese solution is (5-9):(0.5-2):(0.5-3);
[0029] Preferably, the nickel-cobalt-manganese solution comprises nickel salt, cobalt salt and manganese salt;
[0030] Preferably, the nickel salt includes at least one of soluble salts such as nickel sulfate, nickel nitrate, nickel chloride, nickel bromide and nickel iodide;
[0031] Preferably, the cobalt salt includes at least one of soluble salts such as cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt bromide and cobalt iodide;
[0032] Preferably, the manganese salt includes at least one of soluble salts such as manganese sulfate, manganese nitrate, manganese chloride, manganese bromide and manganese iodide.
[0033] In an optional embodiment, the chromium-doped ternary material precursor is prepared under stirring;
[0034] Preferably, the stirring speed is 400-800 rpm.
[0035] In an optional embodiment, the steps (1) and (2) are carried out under a protective atmosphere;
[0036] Preferably, the protective atmosphere comprises nitrogen.
[0037] The present invention provides a chromium-doped ternary material precursor prepared by the above preparation method;
[0038] Preferably, the general formula of the chromium-doped ternary material precursor is Ni x Co y Mn z Cr a (OH)2, where 0.3≤x≤1, 0≤y≤0.3, 0≤z≤0.3, 0.001<a≤0.088, x+y+z≤1;
[0039] In the general formula of the chromium-doped ternary material precursor, x, y, z, and a are the molar ratios of the elements;
[0040] Preferably, the porosity of the chromium-doped ternary material precursor is 5-40%;
[0041] Preferably, based on the mass of the chromium-doped ternary material precursor, the doping amount of chromium is 0.1-5%.
[0042] The present invention provides a method for preparing a ternary material. The chromium-doped ternary material precursor prepared by the preparation method is mixed with a lithium source and sintered to prepare the ternary material.
[0043] Preferably, the mixing further comprises adding additives.
[0044] Preferably, the molar ratio of the chromium-doped ternary material precursor to the lithium element in the lithium source is 1:(1.02-1.05);
[0045] Preferably, the sintering is carried out in an air atmosphere;
[0046] The sintering temperature can be carried out according to the known sintering process in the art. As an example, when the molar proportion of nickel in the ternary material is 50%, the sintering temperature can be selected from 900-1050°C, specifically, the temperature is selected from 900°C, 930°C, 960°C, 1000°C, 1050°C or in the range of any two of the above values; when the molar proportion of nickel in the ternary material is 80%, the sintering temperature is selected from 700-850°C, specifically, the temperature is selected from 700°C, 730°C, 760°C, 790°C, 820°C, 850°C or in the range of any two of the above values. The present invention does not make specific restrictions on the sintering temperature.
[0047] The invention provides a ternary material prepared by the preparation method.
[0048] The present invention provides an application of a ternary material prepared by the above preparation method in a lithium ion battery.
[0049] The technical solution of the present invention has the following advantages:
[0050] 1. The preparation method of the chromium-doped ternary material precursor provided by the present invention comprises the following steps: (1) preparing an intermediate product after reacting a nickel-cobalt-manganese solution; the reaction time is 10-30 hours; (2) adding a chromium salt to the intermediate product, reacting, adjusting the pH of the reaction system, aging, and preparing a chromium-doped ternary material precursor; wherein, before adjusting the pH of the reaction system, the pH is satisfied: pH≤12; after adjusting the pH of the reaction system, the pH is satisfied: 12<pH≤14. The chromium-doped ternary material precursor prepared by the present invention has a porous structure, uniform chromium doping, low residual alkali, stable structure, controllable morphology, uniform particle size, and a simple and easy process. Specifically, the intermediate product obtained after the reaction for 10-30 hours is a secondary particle with poor sphericity and sparse porosity. Under the condition of pH ≤ 12, the nickel-cobalt-manganese solution and the chromium salt are continuously added, and the chromium salt generates a chromium hydroxide precipitate to fill the gaps in the intermediate product without affecting the continued generation of the nickel-cobalt-manganese hydroxide. The reaction is carried out for 30-70 hours to generate secondary spheres with good sphericity and high density. The pH is then adjusted to 12 < pH ≤ 14, and the chromium hydroxide is partially dissolved to form a porous structure, and the undissolved chromium hydroxide is uniformly doped to form a chromium-doped ternary material precursor with uniform chromium doping, good sphericity and a porous structure. The method is simple, the doping effect is good, and the nickel-cobalt-manganese hydroxide will not be dissolved; if the pH value is greater than 14, the nickel-cobalt-manganese hydroxide will dissolve, and the chromium-doped ternary material precursor cannot be obtained.
[0051] The ternary material prepared by using the chromium-doped ternary material precursor prepared by the present invention retains the porous structure and high specific surface area characteristics of the chromium-doped ternary material precursor. The high specific surface area increases the contact area between the ternary material and the electrolyte, thereby improving the lithium ion transmission rate and energy density; the porous structure is conducive to the lithium entering the material during the sintering process, reducing the residual alkali, and is conducive to the formation of a ternary positive electrode material with complete crystallization and uniform element distribution. Compared with the method of doping elements in the sintering process of the prior art, the addition of chromium salts in the process of preparing the precursor of the present invention helps to improve the uniformity of chromium doping.
[0052] 2. The preparation method of the chromium-doped ternary material precursor provided by the present invention utilizes the amphoteric property of chromium hydroxide, that is, chromium hydroxide will react and dissolve in a strong alkaline environment; therefore, by adjusting the pH value, the prepared chromium-doped ternary material precursor can form a porous structure, and the doping amount of the chromium element can be controlled and the chromium element can be uniformly doped, and the operation is simple. The ternary material prepared by the chromium-doped ternary material precursor prepared by the present invention has high initial efficiency and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0054] Figure 1 is a SEM electron microscope image of the ternary material prepared in Example 1 of the present invention;
[0055] Figure 2 is a SEM electron microscope image of the ternary material prepared in Example 2 of the present invention;
[0056] Figure 3 This is a SEM electron microscope image of the ternary material prepared in Comparative Example 1 of the present invention;
[0057] Figure 4 It is a SEM electron microscope image of the ternary material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0058] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0059] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0060] Example 1
[0061] This embodiment provides a method for preparing a chromium-doped ternary material precursor, which is as follows:
[0062] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are mixed in a molar ratio of 6:1:3 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 1.8 mol / L, and the solution is set aside; 2 mol / L ammonia water, 6.6 mol / L sodium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, wherein the volume ratio of the mixed solution to the reactor is 0.4:1, and the pH value of the mixed solution is 11.0.
[0063] (2) nitrogen was introduced into the reactor until it was full, and under the nitrogen atmosphere, nickel-cobalt-manganese solution was introduced with continuous stirring at a flow rate of 10 L / h, and ammonia water and sodium hydroxide solution were introduced to adjust the pH value, and the stirring speed was 600 rpm, and the pH value of the reaction system was adjusted to about 11.3; after stirring for 15 h, an intermediate product was obtained.
[0064] (3) Add nickel-cobalt-manganese solution at a flow rate of 10 L / h, add 1 mol / L chromium nitrate solution at a flow rate of 18 L / h; react at 600 rpm for 55 h, stop feeding, and pass the mixed solution formed by the above-mentioned ammonia water and sodium hydroxide solution into the reaction process to adjust the pH of the reaction system to about 11.3, and the molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions in the nickel-cobalt-manganese solution added in step (3) to the molar ratio of chromium ions is 1:1; then adjust the pH value to about 12.8 with sodium hydroxide solution, stir and age for 8 h, wash, sieve, and demagnetize to obtain a chromium-doped ternary material precursor. Based on the mass of the chromium-doped ternary material precursor, the chromium doping amount is 3.6%; the porosity is 28%.
[0065] This embodiment also provides a method for preparing a ternary material, which is as follows:
[0066] (4) The chromium-doped ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 860° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0067] The SEM electron microscope image of the ternary material prepared in this embodiment is shown in Figure 1 .
[0068] Example 2
[0069] This embodiment provides a method for preparing a chromium-doped ternary material precursor, which is as follows:
[0070] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are mixed in a molar ratio of 8:1:1 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 2.1 mol / L, and the solution is set aside; 3.2 mol / L ammonia water, 10.2 mol / L sodium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, the volume ratio of the mixed solution to the reactor is 0.5:1, and the pH value of the mixed solution is 11.5.
[0071] (2) nitrogen was introduced into the reactor until it was full, and under the nitrogen atmosphere, nickel-cobalt-manganese solution was introduced with continuous stirring at a flow rate of 10 L / h, and ammonia water and sodium hydroxide solution were introduced to adjust the pH value, and the stirring speed was 700 rpm, and the pH value of the reaction system was adjusted to about 11.3; after stirring for 20 h, an intermediate product was obtained.
[0072] (3) Add nickel-cobalt-manganese solution at a flow rate of 10 L / h, add 3.2 mol / L chromium sulfate solution at a flow rate of 2.95 L / h, react at 700 rpm for 55 h, stop feeding, and introduce the mixed solution formed by the above-mentioned ammonia water and sodium hydroxide solution into the reaction process to adjust the pH of the reaction system to about 11.3. The molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions in the nickel-cobalt-manganese solution added in step (3) to the molar ratio of chromium ions is 1:0.899, and then adjust the pH value to about 13.8 with sodium hydroxide solution, stir and age for 15 h, wash, sieve, and demagnetize to obtain a chromium-doped ternary material precursor. Based on the mass of the chromium-doped ternary material precursor, the chromium doping amount is 3.2%; the porosity is 24%.
[0073] This embodiment also provides a method for preparing a ternary material, which is as follows:
[0074] (4) The chromium-doped ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 740° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0075] The SEM electron microscope image of the ternary material prepared in this embodiment is shown in Figure 2 .
[0076] Example 3
[0077] This embodiment provides a method for preparing a chromium-doped ternary material precursor, which is as follows:
[0078] (1) Nickel nitrate, cobalt nitrate and manganese nitrate are mixed in a molar ratio of 7:1:2 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 2.8 mol / L, and the solution is set aside; 4.8 mol / L ammonium bicarbonate solution, 12 mol / L lithium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, wherein the volume ratio of the mixed solution to the reactor is 0.6:1, and the pH value of the mixed solution is 11.8.
[0079] (2) Nitrogen was introduced into the reactor until it was full. Under the nitrogen atmosphere, nickel-cobalt-manganese solution was introduced with continuous stirring at a flow rate of 10 L / h. Ammonium bicarbonate solution and lithium hydroxide solution were introduced to adjust the pH value. The stirring speed was 400 rpm. The pH value of the reaction system was adjusted to about 11.9. After stirring for 28 h, an intermediate product was obtained.
[0080] (3) Add nickel-cobalt-manganese solution at a flow rate of 10 L / h, add 4.8 mol / L chromium trichloride solution at a flow rate of 7 L / h, react at 400 rpm for 35 h, stop feeding, and introduce the mixed solution formed by the above-mentioned ammonium bicarbonate and lithium hydroxide solution into the reaction process to adjust the pH of the reaction system to about 11.9. The total molar ratio of nickel ions, cobalt ions and manganese ions to chromium ions in the nickel-cobalt-manganese solution added in step (3) is 1:1.2, and then adjust the pH value to about 13.8 with lithium hydroxide solution, stir and age for 18 h, wash, sieve, and demagnetize to obtain a chromium-doped ternary material precursor. Based on the mass of the chromium-doped ternary material precursor, the chromium doping amount is 1.4%; the porosity is 15%.
[0081] This embodiment also provides a method for preparing a ternary material, which is as follows:
[0082] (4) The chromium-doped ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 780° C. for 9 h in an oxygen atmosphere to obtain a ternary material.
[0083] Example 4
[0084] This embodiment provides a method for preparing a chromium-doped ternary material precursor, which is as follows:
[0085] (1) Nickel nitrate, cobalt nitrate and manganese nitrate are mixed in a molar ratio of 6.7:0.8:2.5 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 2.5 mol / L, and the solution is set aside; 4.0 mol / L urea solution, 4 mol / L potassium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, wherein the volume ratio of the mixed solution to the reactor is 0.3:1, and the pH value of the mixed solution is 10.8.
[0086] (2) Nitrogen was introduced into the reactor until it was full. Under the nitrogen atmosphere, nickel-cobalt-manganese solution was introduced with continuous stirring at a flow rate of 10 L / h. Urea solution and potassium hydroxide solution were introduced to adjust the pH value. The stirring speed was 800 rpm. The pH value of the reaction system was adjusted to about 10.8. After stirring for 10 h, an intermediate product was obtained.
[0087] (3) Add nickel-cobalt-manganese solution at a flow rate of 10 L / h, add 2 mol / L chromium nitrate solution at a flow rate of 13.7 L / h; react at 800 rpm for 70 h, stop feeding, and introduce the mixed solution formed by the above-mentioned urea and potassium hydroxide solution into the reaction process to adjust the pH of the reaction system to about 10.8. The molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions to chromium ions in the nickel-cobalt-manganese solution added in step (3) is 1:1.096; then adjust the pH value to about 12.1 with potassium hydroxide solution, stir and age for 5 h, wash, sieve, and demagnetize to obtain a chromium-doped ternary material precursor. Based on the mass of the chromium-doped ternary material precursor, the chromium doping amount is 5%; the porosity is 33%.
[0088] This embodiment also provides a method for preparing a ternary material, which is as follows:
[0089] (4) The chromium-doped ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 850° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0090] Example 5
[0091] This embodiment provides a method for preparing a chromium-doped ternary material precursor, which is the same as that of Embodiment 1.
[0092] This embodiment also provides a method for preparing a ternary material. Compared with Embodiment 1, the only difference is that in step (4), the chromium-doped ternary material precursor and lithium carbonate are mixed evenly in a high-speed mixer at a molar ratio of 1:0.525, instead of the chromium-doped ternary material precursor and lithium carbonate in Embodiment 1 being mixed evenly in a high-speed mixer at a molar ratio of 1:0.52.
[0093] Comparative Example 1
[0094] This comparative example provides a method for preparing a ternary material precursor, which is as follows:
[0095] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are mixed in a molar ratio of 6:1:3 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 1.8 mol / L, and the solution is set aside; 2 mol / L ammonia water, 6.6 mol / L sodium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, wherein the volume ratio of the mixed solution to the reactor is 0.4:1, and the pH value of the mixed solution is 11.0.
[0096] (2) Nitrogen is introduced into the reactor until it is full. Under the nitrogen atmosphere, nickel-cobalt-manganese solution is introduced and stirred continuously at a flow rate of 10 L / h. Ammonia water and sodium hydroxide solution are introduced to adjust the pH value. The stirring speed is 600 rpm, and the pH value of the reaction system is regulated to be about 11.3. The reaction is carried out at 600 rpm for 70 hours, and the feeding is stopped. The reaction process is introduced into the mixed solution formed by the above-mentioned ammonia water and sodium hydroxide solution to adjust the pH value of the reaction system to about 11.3, and then the pH value is adjusted to about 12.8 with sodium hydroxide solution. Stir and age for 8 hours, wash, sieve, and demagnetize to obtain a ternary material precursor. The porosity is 2.2%.
[0097] This comparative example also provides a method for preparing a ternary material, which is as follows:
[0098] (4) The ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 860° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0099] The SEM electron microscope image of the ternary material prepared in this comparative example is shown in Figure 3 .
[0100] Comparative Example 2
[0101] This comparative example provides a method for preparing a ternary material precursor, which is as follows:
[0102] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are mixed in a molar ratio of 8:1:1 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 2.1 mol / L, and the solution is set aside; 3.2 mol / L ammonia water, 10.2 mol / L sodium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, the volume ratio of the mixed solution to the reactor is 0.5:1, and the pH value of the mixed solution is 11.5.
[0103] (2) Nitrogen is introduced into the reactor until it is full. Under the nitrogen atmosphere, nickel-cobalt-manganese solution is introduced and stirred continuously at a flow rate of 10 L / h. Ammonia water and sodium hydroxide solution are introduced to adjust the pH value. The stirring speed is 700 rpm, and the pH value of the reaction system is regulated to be about 11.3. The reaction is carried out at 700 rpm for 75 hours, and the feeding is stopped. The reaction process is introduced into the mixed solution formed by the above-mentioned ammonia water and sodium hydroxide solution to adjust the pH value of the reaction system to about 11.3, and then the pH value is adjusted to about 13.8 with sodium hydroxide solution. Stir and age for 15 hours, wash, sieve, and demagnetize to obtain a ternary material precursor. The porosity is 3.1%.
[0104] This comparative example also provides a method for preparing a ternary material, which is as follows:
[0105] (4) The ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 740° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0106] The SEM electron microscope image of the ternary material prepared in this comparative example is shown in Figure 4 .
[0107] Comparative Example 3
[0108] This comparative example provides a method for preparing a ternary material precursor, which is as follows:
[0109] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are mixed in a molar ratio of 6:1:3 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 1.8 mol / L, and the solution is set aside; 2 mol / L ammonia water, 6.6 mol / L sodium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, wherein the volume ratio of the mixed solution to the reactor is 0.4:1, and the pH value of the mixed solution is 11.0.
[0110] (2) nitrogen was introduced into the reactor until it was full, and under the nitrogen atmosphere, nickel-cobalt-manganese solution was introduced with continuous stirring at a flow rate of 10 L / h, and ammonia water and sodium hydroxide solution were introduced to adjust the pH value, and the stirring speed was 600 rpm, and the pH value of the reaction system was adjusted to about 11.3; after stirring for 15 h, an intermediate product was obtained.
[0111] (3) Add nickel-cobalt-manganese solution at a flow rate of 10 L / h, add 1 mol / L zinc sulfate solution at a flow rate of 18 L / h; react at 600 rpm for 55 h, stop feeding, and introduce the mixed solution formed by the above-mentioned ammonia water and sodium hydroxide solution into the reaction process to adjust the pH of the reaction system to about 11.3, and the molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions to zinc ions in the nickel-cobalt-manganese solution added in step (3) is 1:1; then adjust the pH value to about 12.8 with sodium hydroxide solution, stir and age for 8 h, wash, sieve, and demagnetize to obtain a ternary material precursor. The porosity is 2.2%.
[0112] This comparative example also provides a method for preparing a ternary material, which is as follows:
[0113] (4) The ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 860° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0114] Comparative Example 4
[0115] This comparative example provides a method for preparing a ternary material precursor, which is as follows:
[0116] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are mixed in a molar ratio of 6:1:3 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 1.8 mol / L, and the solution is set aside; 2 mol / L ammonia water, 6.6 mol / L sodium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, wherein the volume ratio of the mixed solution to the reactor is 0.4:1, and the pH value of the mixed solution is 11.0.
[0117] (2) nitrogen was introduced into the reactor until it was full, and under the nitrogen atmosphere, nickel-cobalt-manganese solution was introduced with continuous stirring at a flow rate of 10 L / h, and ammonia water and sodium hydroxide solution were introduced to adjust the pH value, and the stirring speed was 600 rpm, and the pH value of the reaction system was adjusted to about 11.3; after stirring for 15 h, an intermediate product was obtained.
[0118] (3) Add nickel-cobalt-manganese solution at a flow rate of 10 L / h, add 1 mol / L magnesium sulfate solution at a flow rate of 18 L / h, react at 600 rpm for 55 h, stop feeding, and add the mixed solution formed by the above-mentioned ammonia water and sodium hydroxide solution to adjust the pH of the reaction system to about 11.3. The molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions in the nickel-cobalt-manganese solution added in step (3) to the molar ratio of magnesium ions is 1:1; then adjust the pH value to about 12.8 with sodium hydroxide solution, stir and age for 8 h, wash, sieve, and demagnetize to obtain a ternary material precursor. Based on the mass of the ternary material precursor, the doping amount of magnesium is 28.5%; the porosity is 2.1%.
[0119] This comparative example also provides a method for preparing a ternary material, which is as follows:
[0120] (4) The ternary material precursor and lithium carbonate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52, and sintered at 860° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0121] Comparative Example 5
[0122] This comparative example provides a method for preparing a ternary material precursor, which is as follows:
[0123] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are mixed in a molar ratio of 6:1:3 to prepare a nickel-cobalt-manganese solution (the solvent is water) in which the total molar amount of nickel ions, cobalt ions and manganese ions is 1.8 mol / L, and the solution is set aside; 2 mol / L ammonia water, 6.6 mol / L sodium hydroxide solution and water are mixed to obtain a mixed solution, which is placed in a reactor, wherein the volume ratio of the mixed solution to the reactor is 0.4:1, and the pH value of the mixed solution is 11.0.
[0124] (2) nitrogen was introduced into the reactor until it was full. Under the nitrogen atmosphere, nickel-cobalt-manganese solution was introduced with continuous stirring at a flow rate of 10 L / h. Ammonia water and sodium hydroxide solution were introduced to adjust the pH value. The stirring speed was 600 rpm. The pH value of the reaction system was adjusted to about 11.3. After stirring for 70 h, a precursor was obtained.
[0125] This comparative example also provides a method for preparing a ternary material, which is as follows:
[0126] (3) The precursor, lithium carbonate and chromium sulfate prepared above were mixed evenly in a high-speed mixer at a molar ratio of 1:0.52:0.015, and sintered at 860° C. for 10 h in an oxygen atmosphere to obtain a ternary material.
[0127] Test example
[0128] The ternary materials obtained in the above embodiments and comparative examples are made into batteries, and the specific steps are as follows:
[0129] The ternary material, polyvinylidene fluoride (PVDF), and Super P (SP) were weighed and homogenized according to the mass ratio of 97.2:1.3:1.5, and then the aluminum foil was spread on the coating machine for coating (surface density of 15-17 mg / cm 2 ), put it into an 80℃ forced air drying oven and dry it for 2h; then punch, weigh, bake the electrode, make it into a CR2032 button battery, and finally put the battery into a blue electric test system for electrical performance testing;
[0130] The performance test of the battery prepared above is as follows:
[0131] (1) Specific surface area test method: A. Load 30 mg of the sample to be tested into the sample tube, install the sample tube into the degassing station (the sample tube should be aligned with the port, and the screws should be tightened to ensure a safe seal), put a heating pack on the sample tube, turn on the vacuum pump, and start heating and vacuum degassing; B. Turn off the power, wait for the sample to cool to room temperature, backfill with helium, and after the helium reaches normal pressure, remove the sample and immediately cover it with a rubber stopper, weigh it to 0.1 mg, and record the gross weight of the sample tube (the sample filled with helium). The weight of the sample is the weight of the tube, stopper and filling rod); C. The weight of the sample is measured by the reduction method: the bracket is peeled and zeroed, the sample tube is added with a stopper and counted as m1, the sample is loaded into the sample tube and the stopper is put on and counted as m2, the bracket is zeroed, the sample tube is degassed in the degassing station, and after cooling, the number is m3, and the sample weight is obtained by subtracting m1 from m3; D. The weighed sample tube is placed in the analysis station, liquid nitrogen is added to the Dewar flask, and the adsorption and desorption tests are started to obtain the specific surface area of the sample. The results are shown in Table 1.
[0132] (2) 0.1C first charge and discharge: let stand for 10 seconds, charge at 0.1C to a voltage of 4.4 V, let stand for 10 seconds, discharge at 0.1C to a voltage of 3 V, let stand for 10 seconds; the results are shown in Table 1.
[0133] (3) First effect: The calculation formula is as follows: First effect = 0.1C first discharge / 0.1C first charge. The results are shown in Table 1.
[0134] (4) Cycle retention rate: Step (2) was repeated twice, charging at 0.5C to a voltage of 4.4 V, standing for 10 s, discharging at 0.5C to a voltage of 3 V, standing for 10 s, and cycling 98 times. The cycle retention rate was calculated by the following formula. The results are shown in Table 1.
[0135] Cycle retention rate = 100st discharge gram capacity / 0.5C first discharge
[0136] Table 1
[0137]
[0138] As can be seen from Table 1, the ternary material prepared by the chromium-doped ternary precursor prepared in the present invention has a high specific surface area, high 0.1C first charge, 0.1C first discharge, and first coulombic efficiency after the battery is made, and good cycle retention rate.
[0139] Comparison between Example 1-2 and Comparative Example 1-2 shows that the ternary material prepared by the chromium-doped ternary precursor prepared by the present invention has good performance. This shows that the chromium element ternary material precursor prepared by the amphoteric substance of chromium hydroxide has a good specific surface area, and the prepared battery has a high first charge at 0.1C, a high first discharge at 0.1C, and a high first efficiency, and the cycle retention rate is greatly improved.
[0140] By comparison between Example 1 and Comparative Example 3, during the precursor preparation process, the zinc element, which also has amphoteric properties, will dissolve at a pH value of 10.8-12, and will not generate zinc hydroxide precipitate to fill the gaps, and the finally obtained ternary material has neither zinc doping nor a high specific surface area; compared with Comparative Example 4, the non-amphoteric magnesium element is used instead of the chromium element to prepare the precursor, which will not dissolve at a pH value of 12.1-14.0, cannot form gaps, does not have a high specific surface area, and the doping amount of the magnesium element cannot be controlled by adjusting the pH value; the 0.1C first charge, 0.1C first discharge, and first coulomb efficiency of the ternary material prepared in Comparative Examples 3-4 are all greatly reduced, and the cycle retention rate is significantly reduced; This shows that the chromium element selected by the present invention cannot be replaced by other doping elements.
[0141] By comparison between Example 1 and Comparative Example 5, when chromium salt is added for sintering during the preparation of the ternary material, the obtained ternary material has a low specific surface area, poor 0.1C first charge, 0.1C first discharge and first coulombic efficiency, and a reduced cycle retention rate; this indicates that the present invention adds chromium salt when preparing the precursor to produce a chromium-doped ternary precursor with better doping effect and more excellent preparation method.
[0142] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a chromium-doped ternary material precursor, characterized in that: The steps include: (1) preparing an intermediate product by reacting a nickel-cobalt-manganese solution; the reaction time is 10-30 hours; (2) adding a nickel-cobalt-manganese solution and a chromium salt to the intermediate product simultaneously, reacting, adjusting the pH of the reaction system, and aging to prepare a chromium-doped ternary material precursor; Wherein, before adjusting the pH of the reaction system, the following conditions are met: pH ≤ 12; The pH of the reaction system was adjusted to satisfy: 12<pH≤14.
2. The preparation method according to claim 1, characterized in that: Before adjusting the pH of the reaction system, the pH is 10.8 < pH ≤ 12; and / or, The nickel-cobalt-manganese solution in step (1) and the nickel-cobalt-manganese solution in step (2) have the same concentration.
3. The preparation method according to claim 1, characterized in that: In the step (2), the reaction time is 30-70 hours; Preferably, the chromium salt comprises a soluble chromium salt; Preferably, the soluble chromium salt comprises at least one of chromium nitrate, chromium sulfate and chromium trichloride; Preferably, in step (2), the molar ratio of the total molar amount of nickel ions, cobalt ions and manganese ions in the reaction solution to the chromium ions is 1:(0.8-1.2).
4. The preparation method according to claim 1 or 2, characterized in that: The step (1) further comprises adding at least one of a precipitant and a complexing agent before carrying out the reaction; Preferably, the complexing agent includes at least one of ammonia, urea and ammonium bicarbonate; Preferably, the precipitant comprises at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide; Preferably, the molar ratio of nickel ions, cobalt ions and manganese ions in the nickel-cobalt-manganese solution is (5-9):(0.5-2):(0.5-3); Preferably, the nickel-cobalt-manganese solution comprises nickel salt, cobalt salt and manganese salt; Preferably, the nickel salt includes at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel bromide and nickel iodide; Preferably, the cobalt salt comprises at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt bromide and cobalt iodide; Preferably, the manganese salt includes at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese bromide and manganese iodide.
5. The preparation method according to claim 3 or 4, characterized in that: The chromium-doped ternary material precursor is prepared under stirring; Preferably, the stirring speed is 400-800 rpm.
6. The preparation method according to claim 1, characterized in that: The steps (1) and (2) are carried out under a protective atmosphere; Preferably, the protective atmosphere comprises nitrogen.
7. A chromium-doped ternary material precursor prepared by the preparation method according to any one of claims 1 to 6; Preferably, the porosity of the chromium-doped ternary material precursor is 5-40%; Preferably, based on the mass of the chromium-doped ternary material precursor, the doping amount of chromium is 0.1-5%.
8. A method for preparing a ternary material, characterized in that: The chromium-doped ternary material precursor prepared by the preparation method according to any one of claims 1 to 6 or the chromium-doped ternary material precursor according to claim 7 is mixed with a lithium source and sintered to prepare a ternary material; Preferably, the mixing further comprises adding additives.
9. The ternary material obtained by the preparation method according to claim 8.
10. Use of the ternary material obtained by the preparation method according to claim 8 or the ternary material according to claim 9 in lithium-ion batteries.
Citation Information
Patent Citations
Chromium-doped lithium-nickel-manganese-oxygen material and preparation method thereof, and lithium ion battery containing chromium-doped lithium-nickel-manganese-oxygen material
CN102637867A
Preparation method of metallic-ion-doped lithium-nickel-cobalt-oxygen positive pole material
CN103606675A
Method for preparing chromium-doped ternary material
CN107634217A
Aluminum-doped nickel-cobalt-manganese ternary positive electrode material precursor, preparation method and application thereof
CN112751017A
Chromium-doped lithium manganate positive electrode material, preparation method thereof and electrochemical energy storage device
CN117790774A